Stable Numerical Evaluation of Finite Hankel Transforms and Their Application. (13th November 2014) - Tripathi, Manoj P.; Singh, B. P.; Singh, Om P.
Abstract : A new stable algorithm, based on hat functions for numerical evaluation of Hankel transform of orderν > - 1, is proposed in this paper. The hat basis functions are used as a basis to expand a part of the integrand, r f ( r ), appearing in the Hankel transform integral. This leads to a very simple, efficient, and stable algorithm for the numerical evaluation of Hankel transform. The novelty of our paper is that we give error and stability analysis of the algorithm and corroborate our theoretical findings by various numerical experiments. Finally, an application of the proposed algorithm is given for solving the heat equation in an infinite cylinder with a radiation condition.